Structure and magnetic-field induced effects in Mn-Ni(Fe)-Sn metamagnetic shape memory alloys - Sasmaz, M.; Chernenko, V. A.; Martinez, E.; Lazpita, P.; Barandiaran, J. M.; Gutierrez, J.; Aydogdu, Y. (Elsevier, 2015)
Martensitic structures, transformation behavior and some magnetic properties of a new series of Mn49Ni42-xFexSn9 (x = 0 -4 at.%) metamagnetic shape memory alloys have been studied as a function of Fe content and magnetic field. Fe doping decreased sharply the martensitic transformation temperatures. The XRD patterns showed different phases including orthorhombic structure, the L2(1) cubic phase and the fcc gamma-phase at room temperature depending on Fe content. The magnetization curves, M-H, exhibited obvious metamagnetic transitions. (C) 2015 The Authors. Published by Elsevier Ltd.
14th International Conference on Martensitic Transformations (ICOMAT) -- JUL 06-11, 2014 -- Bilbao, SPAIN
Keywords: MnNiSnFe Metamagnetic shape memory alloys; crystal structure; martensitic transformation